Preparation and characterization of Fe-doped TiO2 powders for solar light response and photocatalytic applications - Ibram Ganesh; Polkampally P. Kumar; Abhishek K. Gupta; Panakati S.C. Sekhar; Kalathur Radha; Gadhe Padmanabham; Govindan Sundararajan (Processing and Application of Ceramics, 2012)
Different amounts of Fe-doped TiO2 (with 0.1 to 10 wt.% Fe) powders were prepared at temperatures in the range of 400 and 800 °C following a conventional co-precipitation technique and were thoroughly characterized by means of X-ray diffraction (XRD), Fourier-transform infrared (FT-IR), Fourier-transform Raman (FT-Raman), diffuse reflectance spectroscopy (DRS), BET surface area, zeta potential and flat band potential measurements. Photocatalytic ability of Fe-doped TiO2 powders was evaluated by means of methylene blue (MB) degradation experiments conducted under the irradiation of simulated solar light. Characterization results suggested that as a dopant Fe stabilized TiO2 in the form of anatase phase, reduced its band gap energy and adjusted its flat band potentials in such a way that these powders can be employed for photoelectrolysis of water into hydrogen and oxygen in photoelectrochemical (PEC) cells. The 0.1 wt.% Fe-doped TiO2 exhibited highest activity in the photocatalytic degradation of MB. The kinetic studies revealed that the MB degradation reaction follows the Langmuir-Hinshelwood first order reaction rate.